Supporting post-COVID-19 economic recovery in Southeast Asia. - Seng, Bingxun; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
ADB has identified three well established sectors that need to be transformed or improved: tourism, agro-processing, and garments; and two evolving sectors with high potential for future growth: electronics and digital trade. For each of these sectors, the brief discusses the current structural challenges, outlines the impacts of COVID-19, and identifies the policy responses needed.
Keywords: COVID-19,Disease -- Economic aspects; Health care reform; Electronic book